2018
DOI: 10.1021/acs.organomet.8b00334
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Reduction by Iron Hangman Porphyrins

Abstract: Iron hangman porphyrins with phenol, guanidinium, and sulfonic acid proton donor groups placed above the Fe porphyrin platform reduce CO2 to CO with Faradaic efficiencies >93%. Computations show that the activation of CO2 at the Fe center is enhanced by the hanging group. Intramolecular hydrogen bonding from the phenol and guanidinium groups results in a 2.1–6.6 kcal/mol stabilization of CO2 within the hangman pocket; the hanging sulfonate group is deprotonated, thus resulting in destabilization of the CO2 add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
158
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(165 citation statements)
references
References 42 publications
3
158
4
Order By: Relevance
“…[30,31] This family primarily comprises iron porphyrins, which are robust and readily derivable, such that one can explore and elucidate the structure/proprieties of substituent effects and uncover the parameters governing the CO 2 electroreduction rate, turnover, and selectivity. [30,31] This family primarily comprises iron porphyrins, which are robust and readily derivable, such that one can explore and elucidate the structure/proprieties of substituent effects and uncover the parameters governing the CO 2 electroreduction rate, turnover, and selectivity.…”
Section: Iron-based Catalystsmentioning
confidence: 99%
“…[30,31] This family primarily comprises iron porphyrins, which are robust and readily derivable, such that one can explore and elucidate the structure/proprieties of substituent effects and uncover the parameters governing the CO 2 electroreduction rate, turnover, and selectivity. [30,31] This family primarily comprises iron porphyrins, which are robust and readily derivable, such that one can explore and elucidate the structure/proprieties of substituent effects and uncover the parameters governing the CO 2 electroreduction rate, turnover, and selectivity.…”
Section: Iron-based Catalystsmentioning
confidence: 99%
“…[10][11][12] Implementing these functionalities in the second coordination sphere [5] such as local proton source, (i.e. phenols, [13][14][15] carboxylic acids [16] ), H-bond donors (amines, [17] amides, [18] guanidine [19] ) and reaction intermediate stabilizers (ammonium cations, [20] and imidazolium moieties [21,22] ) have successfully lead to decrease significantly the overpotential while improving the catalytic turnover numbers (TONs) and frequencies (TOFs).…”
mentioning
confidence: 99%
“…These two catalysts were designed starting from a 5,10,15,20-tetrakis(2aminophenyl)porphyrin (TAPP) with an abab configuration (Scheme 1). Unlike studies utilizing hangman, [18,19] and picket-fence [13,22] structures of porphyrins for CO 2 reduction, this atropoisomer was chosen with the target to provide two sets of hydrogen bonding network in a trans fashion towards a metal bound CO 2 molecule and at the same time to confer two identical chemical faces on each side of the porphyrin molecular platform. Our results showed that the FeTPP-Am catalyst had no marked enhancement on the electrocatalytic activity of CO 2 reduction when compared to the tetraphenylporphyrin (FeTPP) derivative.…”
mentioning
confidence: 99%
“…Attempts to obtain single crystals of 1-Cl suitable for X-ray structure analysis were unsuccessful. Fortunately, the reaction of FeCl 2 with various porphyrins under the same conditions has been well documented in the literature, [38][39][40] showing that a Fe III ion is incorporated at the center of the porphyrin ring with an axial chloride ligand. The Fe III ion is obtained from the oxidation of Fe II with air.…”
mentioning
confidence: 81%
“…Fe porphyrins have received considerable attention among these catalysts . They show high activity and stability for the selective CO 2 ‐to‐CO conversion, and they provide an ideal platform to investigate various structural effects on CO 2 RR, because the meso ‐substituents of the porphyrin ring can be systematically modified to introduce different acid/base groups and positively/negatively charged moieties .…”
Section: Figurementioning
confidence: 99%